New introgressive forms of cultivated barley obtained on the basis of interspecific hybrids Hordeum vulgare L. × Hordeum bulbosum L. - G. I. Pendinen (Биотехнология и селекция растений, 2022)
Background. The use of alien genetic material of bulbous barley Hordeum bulbosum L. to increase the diversity of cultivated barley Hordeum vulgare L. is an important task, since H. bulbosum is characterized by a number of valuable traits. One of the ways to use the genetic potential of bulbous barley is the interspecific hybridization and obtaining fertile introgressive lines of H. vulgare based on interspecific hybrids. The aim of the study was to obtain new introgressive forms of spring barley using interspecific triploid (HvHbHb) and tetraploid (HbHbHvHv) hybrids of cultivated barley with bulbous barley to expand the collection of introgressive lines of H. vulgare. Materials and methods. To create new introgressive forms, diploid barley H. vulgare (2x) cv. ‘Roland’,  was crossed with interspecific hybrids H. vulgare cv. ‘Roland’(2x) × H. bulbosum W851 (4х) (HvHbHb), and H. bulbosum A17 (4x) × H. vulgare ‘Borwina’ (4x) (HbHbHvHv). Cultivated barley forms with introgression of the bulbous barley genetic material were selected from the offspring from these crosses; then the selection was continued in two progenies from self-pollination of selected BC1 plants with three alien introgressions. Identification and localization of introgressions was carried out using the method of fluorescent in situ hybridization (GISH and FISH with chromosome-specific markers). Results. The crossing of cultivated barley with triploid and tetraploid interspecific hybrids H. vulgare × H. bulbosum yielded new forms of cultivated barley with recombinant chromosomes, among which two plants with three terminal introgressions of the genetic material of bulbous barley were identified. The first plant, derived from a triploid hybrid, showed introgressions in chromosomes 5HL, 1HL and 3HS. When two homologues with the 5HL introgression of the initial size are combined in the karyotype, the lethality of seedlings is observed in the offspring plants. In the second plant obtained on the basis of a tetraploid hybrid introgression was revealed in chromosomes 5HL, 2HL, and 7HS. In the offspring from self-pollination of this form, the presence of the 2HL introgression of the original size in both homologues led to plant sterility. Forms with a change in size of the introgression in 5HL and 3HS in the offspring of the first plant and with a change in size of the introgression in 2HL in the offspring of the second plant were detected, which indicated that meiotic recombination had occurred in those chromosome regions in BC1 plants. Conclusions A barley plant with the introgression of bulbous barley chromatin into chromosomes 1HL, 5HL, and 3HS of cultivated barley was identified in the offspring from a cross of cultivated barley with a triploid interspecific hybrid H. vulgare × H. bulbosum. In crosses with a tetraploid interspecific hybrid, a barley plant with the introgression into chromosomes 2HL, 5HL, and 7HS was found. On the basis of ‘Roland’ spring barley cultivar, two series of new introgressive forms of H. vulgare with various combinations of recombinant chromosomes have been created.